Revisiting The Impact of Occupational Segregation on the Gender Earnings Gap in Malaysia - Ching Goy, Siew; Johnes, Geraint (Universiti Malaysia Sarawak, (UNIMAS), 2012)
More women participate in the labour force nowadays than in the past. However, they do not join the workforce as equal members. Segregation in occupational distribution and pay differentials between men and women remain pervasive. This article uses data from the Malaysian Population and Family Survey 2004 to shed light on the inequality in earnings based on the framework developed by Brown et al. (1980). The empirical results suggest that segregation per se works to the advantage of women. A surprising finding is that the intra-occupational component, which is unjustified by reference to observed characteristics, is responsible for the overall earnings gap. It is likely that the within-occupational earnings discrimination reflects hierarchical segregation. Also, a portion of the earnings gap is attributed to a sample selection effect. Our results suggest that a timely policy intervention would aim to find ways of improving the returns to characteristics earned by women in a given occupation.